Improvement on within wafer and wafer-to-wafer uniformity by chemical mechanical polishing (CMP) - Wu, Hong Ying. (2008)
CMP plays a very important role to realize multi-level metallization which is dependent on the ability to effectively planarize the dielectric layers, which insulate the multi-level interconnects. Despite this advantage, the process still suffer from large global non-uniformity within a die and across a wafer or between wafers.